Efficient calculation of self - Leung, K.W.
This paper presents an analysis of a monopole in free space. The result is given in a concise form that facilitates numerical programming. Moreover, the calculation involves no numerical integration and, thus, the computation is extremely fast
Keywords: MoM analysis; Free space monopole antenna; Moment method; Programming. numerical